2019
DOI: 10.1038/s41380-019-0393-5
|View full text |Cite|
|
Sign up to set email alerts
|

MMP9/RAGE pathway overactivation mediates redox dysregulation and neuroinflammation, leading to inhibitory/excitatory imbalance: a reverse translation study in schizophrenia patients

Abstract: Various mechanisms involved in schizophrenia pathophysiology, such as dopamine dysregulation, glutamate/NMDA receptor dysfunction, neuroinflammation or redox imbalance, all appear to converge towards an oxidative stress "hub" affecting parvalbumine interneurones (PVI) and their perineuronal nets (PNN) (Lancet Psychiatry. 2015;2:258-70); (Nat Rev Neurosci. 2016;17:125-34). We aim to investigate underlying mechanisms linking oxidative stress with neuroinflammatory and their long-lasting harmful consequences. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
90
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 85 publications
(103 reference statements)
3
90
0
Order By: Relevance
“…Dopaminergic hyperactivity in the striatum is thought to underlie the symptoms of schizophrenia, particularly psychosis [2][3][4][5]. Supporting this, 3,4-dihydroxy-6- 18 F-fluoro-l-phenylalanine ([ 18 F]-FDOPA) positron emission tomography (PET) imaging studies have revealed higher striatal dopamine synthesis capacity in patients with schizophrenia [6][7][8][9]. Furthermore, increased dopamine synthesis capacity is associated with both the development of psychosis [10] and the severity of symptoms [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dopaminergic hyperactivity in the striatum is thought to underlie the symptoms of schizophrenia, particularly psychosis [2][3][4][5]. Supporting this, 3,4-dihydroxy-6- 18 F-fluoro-l-phenylalanine ([ 18 F]-FDOPA) positron emission tomography (PET) imaging studies have revealed higher striatal dopamine synthesis capacity in patients with schizophrenia [6][7][8][9]. Furthermore, increased dopamine synthesis capacity is associated with both the development of psychosis [10] and the severity of symptoms [11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to dopaminergic dysfunction, the glutamate hypothesis of schizophrenia has developed from the observations that N-methyl-D-aspartate receptor (NMDAR) antagonists such as ketamine induce psychotic symptoms in healthy humans and exacerbate symptoms in patients [14,15]. Furthermore, schizophrenia is associated with a reduction in parvalbumin (PV)-expressing GABAergic interneurons, which are regulated by NMDARs in the cortex and hippocampus [16][17][18]. It has been suggested that impaired PV neuronal function in the cortex and hippocampus may lead to disinhibition of mesostriatal dopamine neuron activity via a polysynaptic pathway [19].…”
Section: Introductionmentioning
confidence: 99%
“…(*P < 0.05) nervous system in a knockout mouse study [31]. In addition, MMP9 indirectly regulates PNNs via the activation of advanced glycation end-products and inflammatory cytokine cascades [32]. The increased expression level of MMP9 in the noise group might have decreased PNN and brevican expression, thereby influencing the neuroplastic changes associated with auditory sensory deficits after noise exposure in this study.…”
Section: Discussionmentioning
confidence: 66%
“…In addition to dopaminergic dysfunction, the glutamate hypothesis of schizophrenia has developed from the observations that N-methyl-D-aspartate receptor (NMDAR) antagonists such as ketamine induce psychotic symptoms in healthy humans and exacerbate symptoms in patients (14, 15). Furthermore, schizophrenia is associated with a reduction in parvalbumin (PV)-expressing GABAergic interneurons, which are regulated by NMDAR in the cortex and hippocampus (1618). It has been suggested that impaired PV neuronal function in the cortex and hippocampus may lead to disinhibition of mesostriatal dopamine neuron activity via a polysynaptic pathway (19).…”
Section: Introductionmentioning
confidence: 99%